Pengembangan Digital Marketing Dalam Peningkatan Omset Pada Deka Craft Desa Penggarit Kecamatan Taman Pemalang - Handayani, Tri; Erfandi, Eli; Murdianingsih, Dian; Dewi, Yanuar Kusuma (LPPM Universitas Muhadi Setiabudi, 2024)
This community service activity was carried out at the Deka Craft wood craft, Penggarit Village, Sirandu Hamlet, Pemalang Regency. It aims to help empower the economy through business management, especially in Deka Craft. This assistance is focused on 1.) Marketing Management, namely: effective marketing and promotion through social media. 2.) Business Management Assistance, namely: upgrading MSME banners, improving product packaging during the delivery process. At the end of this mentoring activity, you get banners and logo stickers along with packaging boxes so that when shipping goods it is safer and more attractive and promotional media through social media.